2018
DOI: 10.1187/cbe.17-06-0106
|View full text |Cite|
|
Sign up to set email alerts
|

Collectively Improving Our Teaching: Attempting Biology Department–wide Professional Development in Scientific Teaching

Abstract: A collaborative professional development program that engaged nearly 90% of faculty in a biology department in more than 40 hours of training on scientific teaching was instituted. Participating instructors integrated active learning in their courses, as shown through a variety of methods, and reported positive effects on teaching and departmental community.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 46 publications
2
41
0
Order By: Relevance
“…, 2016 ). This, coupled with the research by Owens et al. (2018) , who showed that professional development for faculty helped them make significant changes in their course design, makes the case for developing professional development courses for lecturers and student advisors to facilitate the explicit teaching and demonstration of SRL skills inside and outside the classroom.…”
Section: Discussionmentioning
confidence: 98%
“…, 2016 ). This, coupled with the research by Owens et al. (2018) , who showed that professional development for faculty helped them make significant changes in their course design, makes the case for developing professional development courses for lecturers and student advisors to facilitate the explicit teaching and demonstration of SRL skills inside and outside the classroom.…”
Section: Discussionmentioning
confidence: 98%
“…Cohort A faculty participated in two 5-day summer institutes, three Saturday workshops during each of two academic years, and monthly meetings of faculty professional learning communities (PLCs). The adoption of a 2-year model with embedded PLC's was a response to research showing the efficacy of longer-term, work-embedded interventions over "one-shot" workshops (Henderson et al, 2011;Owens et al, 2018;Wei, Darling-Hammond, Andree, Richardson, & Orphanos, 2009). Participants included contingent faculty as well as tenure track faculty at the assistant, associate, and full professor ranks at all three institutions.…”
Section: Faculty Development In Stemmentioning
confidence: 99%
“…TPD efforts can be powerful influencers to improve instructor delivery of evidence-based teaching practices (e.g., Owens et al, 2018;Pelletreau et al, 2018), but only if instructors participate. Therefore, this essay is not focused on the practices or principles of TPD, but rather on how to get instructors (faculty members, postdocs, graduate students) who are currently not motivated to attend TPD, to go to existing sessions and engage in reforming their teaching practices.…”
Section: Tpd In Higher Educationmentioning
confidence: 99%
“…Many current successful TPD programs overcome barriers to participation by using external incentives, such as department heads personally asking instructors to participate, acquiring funds to financially incentivize participation, or joining in a collaborative publication (Owens et al, 2018;Pelletreau et al, 2018). These strategies can be used to great effect when motivating instructors to attend a specific professional development program with specific objectives and outcomes.…”
Section: Barriers To Participating In Teaching Professional Developmentmentioning
confidence: 99%